Systemic treatment type is not associated with abnormal post-treatment noninvasive liver stiffness measurement in psoriasis - Yue Xiao; Jingya Gao; Yiyi Wang; Dan Hao; Wei Yan; Dingke Wen; Siyi Zeng; Shiqi Yang; Yingyu Shi; Wei Li (Frontiers in Immunology)
BackgroundPsoriasis is commonly associated with metabolic dysfunction-associated steatotic liver disease, raising concerns about the hepatic effects of systemic treatments on psoriasis and its comorbid conditions. This study evaluates liver stiffness measurement (LSM) alterations and identifies predictors of abnormal LSM in psoriatic patients following systemic treatments, including biologics and methotrexate.MethodsThis prospective cohort study is based on the PSOWCH database (Psoriasis Cohort of West China Hospital). We initially included psoriatic patients who had undergone sound touch elastography (STE), then recruited patients who had STE before systemic treatment and reassessed them after at least six months. Three treatment subgroups were formed (interleukin inhibitors, tumor necrosis factor inhibitors, and methotrexate), classifying post-treatment STE outcomes using threshold values of 6.5 kPa and 10.3 kPa.ResultsAmong the 52 recruited patients, overall STE values significantly increased during follow-up. Univariate regression analysis showed that age, gender, psoriasis severity, psoriatic arthritis status, and current treatment type were not significantly correlated with abnormal STE outcomes at cutoff values of 6.5 kPa and 10.3 kPa. In the multivariate model, body mass index (BMI) was identified as a risk factor for post-treatment STE ≥ 6.5 kPa (odds ratio [OR], 1.26; 95% CI, 1.04 to 1.60, P=0.031).ConclusionsThis exploratory study reveals that systemic treatment type is not associated with abnormal post-treatment LSM. However, a significant association exists between BMI and abnormal LSM outcomes. These findings highlight the critical importance of BMI management in therapeutic interventions for psoriasis.